(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
this article describes a brief understanding of the duties and responsibilities of an educator teacher who leads students studying in our country in organizing the leadership of extracurricular and extracurricular activities.